2015
DOI: 10.1371/journal.pone.0138922
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship between Individual Differences in Analytic Thinking and Religious Belief: Evidence That Measurement Order Moderates Their Inverse Correlation

Abstract: Prior research has found that persons who favor more analytic modes of thought are less religious. We propose that individual differences in analytic thought are associated with reduced religious beliefs particularly when analytic thought is measured (hence, primed) first. The current study provides a direct replication of prior evidence that individual differences in analytic thinking are negatively related to religious beliefs when analytic thought is measured before religious beliefs. When religious belief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
13
2
1
Order By: Relevance
“…Crucially, this association was evident despite the fact that religiosity and analytic thinking were measured in separate sessions. These results contradict Finley et al’s [ 24 ] hypothesis that the association between religiosity and analytic thinking requires participants to be put in an analytic mindset when reporting their religiosity. In each of these four studies, our religious belief scale was administered in a mass testing survey along with a variety of scales (presented in a random order for each participant; see S1 Text ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Crucially, this association was evident despite the fact that religiosity and analytic thinking were measured in separate sessions. These results contradict Finley et al’s [ 24 ] hypothesis that the association between religiosity and analytic thinking requires participants to be put in an analytic mindset when reporting their religiosity. In each of these four studies, our religious belief scale was administered in a mass testing survey along with a variety of scales (presented in a random order for each participant; see S1 Text ).…”
Section: Discussioncontrasting
confidence: 99%
“…As a procedure for identifying candidate studies, the primary author manually searched each article that cited any of the three original CRT/religiosity studies [ 4 , 12 , 13 ] via Google Scholar . Thirty-five studies were identified, including Finley et al’s [ 24 ] two conditions (which we treat as two studies for the purpose of this analysis), the four studies from the present paper, an unpublished study from a Master’s thesis [ 26 ], and 8 studies (across 2 articles, [ 28 , 29 ]) that were published after Finley et al Thirty-one of these studies found a statistically significant negative association between analytic thinking and religious belief, and four did not. However, two of these non-significant results ( r ’s = -.15 and -.23 from [ 22 ] and [ 29 ], respectively) were within the range of previous work but had relatively small samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We bring evidence that it is important to distinguish between group differences in the CRT that reflect intuition inhibition, and can inform the dual process models, from the differences that do not tell much about group differences and hence are not informing any new developments of the models. Consider for example the finding that religious believers do not perform as well as nonbelievers on the CRT (Gervais & Norenzayan, 2012), (Finley, Tang, & Schmeichel, 2015), (Pennycook, Ross, Koehler, & Fugelsang, 2016). This result has important theoretical implications because it provides us with new insights about how religious believers process information, and challenges us to apply the dual-process model to the complex domain of religious cognition.…”
Section: Anxiety (Partially) Mediates Gender Differences In the Crtmentioning
confidence: 99%